Assumptions of Universitas PGRI Palembang Students Towards E-Learning Management Information Systems - Meilia Rosani; Neta Dian Lestari; Reva Maria Valianti; Januardi Januardi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2023)
The learning information system (SISFO) owned by PGRI Palembang University, education in the era of society 5.0 has become an interest and attraction for students to learn. Including the implementation of the MBKM Curriculum which requires lecturers and students to use information systems to facilitate the learning process. Even so, various difficulties and challenges that continue to arise make the learning process in the era of Society 5.0 less efficient and effective. Apart from that, there are several challenges that must be overcome in learning, especially in obtaining material. At PGRI Palembang University, virtual world learning is known as SISFO E-Learning. The aim of this research is to better understand students' assumptions in learning using the PGRI Palembang University Learning Information System (SISFO) in the MBKM Curriculum in the 2021/2022 academic year. Based on the average results of these indicators, the percentage achieved in the High category was 76.63%.